Lettuce growth and water consumption in NFT hydroponic system using brackish water - Hammady R. Soares; Ênio F. de F. e Silva; Gerônimo F. da Silva; Elvira M. R. Pedrosa; Mario M. Rolim; Alexandre N. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
The qualitative aspects of water, such as the preparation or replenishment of the nutrient solution, are critical to the success of hydroponic crops. Therefore, the aim of this study was to evaluate the behavior of “Americana” lettuce (cv. Tainá) under increasing levels of saline stress (0.2 - control, 1.2, 2.2, 3.2, 4.2 and 5.2 dS m-1), replenishing the evapotranspiration with brackish water in Experiment I and supply water (0.2 dS m-1) in Experiment II, both used in the preparation of the nutrient solution. In both experiments, the treatments were arranged in a randomized block design, with six treatments and four replicates. Shoot fresh matter, shoot dry matter and leaf area in Experiment I suffered reductions of 15.22, 12.67 and 15.6% per unit increase of EC, respectively. In Experiment II, reductions of 8.01, 6.90 and 8.14% were observed for the same variables, respectively. In Experiments I and II, linear decrease in water consumption due to the increase in salinity was observed, with reductions of 8.83 and 5.63% for each unit increase of electrical conductivity of water when the evapotranspiration was replenished using brackish and supply water, respectively.